Synthesis of Antimony Sulphoiodide by CVD and its Characterization - Dubey, Harish K.; Deshmukh, L. P.; Kshirsagar, D. E.; Jadhav, Vijay S.; Sharon, Madhuri; Sharon, Maheshwar (Journal of Nepal Chemical Society, 2013)
Antimony Sulphoiodide is most widely studied compound in group V-VI-VII family due to its largenumber of properties. Varoius methods of synthesis have been reported. We are the first to reportsynthesis of shiny SbSI crystals by the Chemical Vapor Deposition (CVD) technique using powder ofAntimony, Sulphur and Iodine as the starting material. Needle shaped thin crystals of SbSI were foundgrown vertically on the walls of the quartz tube. Characterizations of the sample were done usingdifferent techniques such as powder X-ray diffraction (XRD), scanning electron microscopy (SEM)and energy dispersive X-ray analysis (EDAX). The charcteristcs peaks in Raman scattering plots (0-500 cm-1) match with the reported results. The compound exibits high resitivity at room temperaturein the order of 10-7 Ω-cm and dielectric constant in the order of 10-3 measured at 1 KHz. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9381 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 111-117 Uploaded date: 12/20/2013